FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS JAILOLO - Mahmud, Ekawati; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: Pregnancy is an important period that affects the mother's physical and psychological well-being. Anxiety in pregnant women, especially in the third trimester, can have a negative impact on the health of the mother and fetus. Identifying factors that influence anxiety in pregnant women in certain areas, such as the Jailolo Community Health Center, is important for developing appropriate interventions. Objective: This study aims to identify and analyze factors that influence the level of anxiety in third trimester pregnant women at the Jailolo Community Health Center. Method: This study used a cross-sectional design with a sample of 50 third trimester pregnant women selected by purposive sampling. Data was collected through a questionnaire consisting of demographic questions and an anxiety scale. Data analysis was carried out using the chi-square statistical test and logistic regression to determine factors that significantly influence anxiety. Results: The results of the study showed that factors that were significantly related to the level of anxiety in third trimester pregnant women at the Jailolo Community Health Center included level of education, social support, history of previous pregnancies, and economic status. Mothers with low education, lack of social support, a history of problematic pregnancies, and low economic status tend to have higher levels of anxiety. Conclusion: The level of anxiety in third trimester pregnant women is influenced by various demographic and social factors. Interventions focused on improving health education, increasing social support, and improving economic conditions can help reduce anxiety in pregnant women at the Jailolo Community Health Center.